2013
DOI: 10.1037/a0031581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 10-day oxytocin trial in older adults on health and well-being.

Abstract: The neuropeptide oxytocin (OT) modulates functioning of the hypothalamic-pituitary-adrenal (HPA) axis and regulates a range of social processes. Clinical studies have used intranasal OT administration to treat symptoms arising from a number of psychiatric disorders including autism, schizophrenia, and depression. Most of this research, however, has been based on single dose treatments of OT in younger adult populations. The present study examined the impact on the health and psychological well-being of a 10-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 73 publications
5
41
0
1
Order By: Relevance
“…Researchers are now beginning to examine the biochemical basis of wellbeing and one study by Barraza, Grewal, Ropacki, Perez, Gonzalez, and Zak (2013) examined the effect of a 10-day trial of the neuropeptide oxytocin on the wellbeing of a group of 23 communitydwelling elderly people. Oxytocin is a hormone hypothesized to regulate social processes, particularly the motivation to socially engage and actual behavioral engagement.…”
Section: Gratitude and The Elderlymentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers are now beginning to examine the biochemical basis of wellbeing and one study by Barraza, Grewal, Ropacki, Perez, Gonzalez, and Zak (2013) examined the effect of a 10-day trial of the neuropeptide oxytocin on the wellbeing of a group of 23 communitydwelling elderly people. Oxytocin is a hormone hypothesized to regulate social processes, particularly the motivation to socially engage and actual behavioral engagement.…”
Section: Gratitude and The Elderlymentioning
confidence: 99%
“…reported that gratitude appears to motivate social behavior. Barraza et al (2013) carried out a randomized trial with participants of mean age 80 years.…”
Section: Gratitude and The Elderlymentioning
confidence: 99%
“…[10][11][12] In recent human studies, OT has been shown to be associated with social bonding, [13][14][15][16] trust, [17][18][19][20] altruism and generosity, 21 parochial altruism, 22 cooperation, 23 empathy, 24,25 and well-being. 26 These findings have been established in studies measuring endogenous (circulating) as well as exogenously administered intranasal OT. 27 The various functions attributed to OT have led to increased interest in understanding the role of OT as a mediator of prosocial behaviors, with implications for promoting health and well-being in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Definitely the argument to bring to light the psychophysiology of resilience, it's the potentiality to promote Well-being and provide most effective insight about the extraordinary body of resilient individuals "what are made of" and "how it recovers homeostasis or balances itself" and knowing that exists already in the market oxytocin nasal spray and scientific literature indicates benefits of using it for PTSD (Eidelman-Rothman et al, 2015) and other disorders as autism spectrum, schizophrenia and depression (Barraza et al, 2013), we aim to contribute with this research project to the development of new pharmacotherapy and new benefits of use of those existing.…”
Section: Previous Considerationsmentioning
confidence: 99%
“…Wu et al (2013) still indicate the importance and necessity to study the inter-relation between biologic and genetic mechanisms, and particularly of the neuroendocrine, hippocampal, cortical, reward and serotoninergic systems to establish and maintain resilience. Pfau&Russo (2015) advise that a budding area of research with great therapeutic promise involves the study of resilience, the adaptive maintenance of normal physiology and behavior despite exposure to marked psychological stress, and recommend that an enhanced focus on resilient subjects may enable us to harness mechanisms of resilience in the body and brain for the successful treatment of stress-related disorders and knowing that exists already in the market oxytocin nasal spray and scientific literature indicates benefits of using it for PTSD (Eidelman-Rothman et al, 2015) and other disorders as autism spectrum, schizophrenia and depression (Barraza et al, 2013), we aim to contribute with this research project to the development of new pharmacotherapy and new bene-fits of use of those existing, which confirm the pertinence and major interest of this pioneer research project.…”
Section: Literature Reviewmentioning
confidence: 99%